Differences in the Structure of the Emotional Component of Safe Behavior Regulation in Students with Intact and Impaired Intelligence - Fatikhova L.F; Sayfutdiyarova E.F (Moscow State University of Psychology and Education, 2021)
The article is devoted to the problem of studying mechanisms of responding to danger and recognizing emotional states of participants in dangerous situations in the process of regulating safe behavior in students of adolescent and youthful age with intact and impaired intelligence. It was assumed that there are differences in the emotional component structure of psychological safety among students, due to age-related characteristics (adolescence and youth) and the presence (absence) of intellectual disabilities in these students. The study involved students of adolescent and youthful age with intact and impaired intelligence. To achieve the goal of the study, the authors used a questionnaire test by V.G. Maralov to identify types of attitude towards danger, the methodology "Emotional attitude of adolescents to dangerous situations", and the methodology "Adolescents in dangerous situations", designed to study the ability to recognize emotional states of people in dangerous situations. Through correlation analysis, the authors revealed the relationships between the elements of the emotional component in the students' perception of a dangerous situation, namely, between the parameters of emotional attitude to dangerous situations, and the ability to recognize the emotional states of participants in dangerous situation. Such relationships are more represented in adolescents with impaired intelligence than in their peers without intellectual disabilities. The results of the study allow us to state the differences in the mechanisms of formation of psychological safety in students of adolescent and youthful age with impaired and intact intelligence. The data obtained can be used in the development of programs for formation of psychological mechanisms that allow students to avoid dangerous situations.